TZSBLC With Optimized PI Controller Design for Grid Tied PV Based Electric Vehicle - AranGlenn J. (International Journal of Electrical Machine Analysis and Design, 2025)
Around the world, about 18% pre-mature births and 3.7 million losses of lives occur due to air pollution and 29% of it is contributed by the Internal Combustion Engine (ICE) based vehicles, which consumes fossil fuels for its functioning. Moreover, the increased demand for fossil fuels, as well as the growth in concerns regarding the environmentally friendly and zero-emission transportation, lead to the introduction of electric Vehicles (EVs). The increased growth in EV sales starting from 3.1 million (2020) to 14 million (2025), resulted in the necessity for better EV charging facilities. The increased cost and short life span of batteries leads to high EV reliability issues, restricted driving range and charging time. Besides, the vast penetration of EVs creates high strain on the grid, at the time of charging, as EV involves consumption of huge energy within a short duration of time. These concerns corresponding to EVs are eradicated with the integration of RES (Renewable Energy Sources) like Solar, wind, tidal, biomass, etc. into the EV infrastructure and it gains increased popularity, as they decrease the grid burdens, GHG (Green House Gas) emissions and charging costs. A novel Trans Z-source Luo converter is used to enhance the PV output voltage thereby lessening the number of PV panels used. The proposed converter exhibits the benefits like excellent efficiency, lesser voltage stress and high conversion range. The operation of the proposed converter is regulated with the aid of Lion Grey Wolf Optimized Proportional Integral (LGWO-PI) controller which significantly strengthens the converter operation in terms of settling time, total harmonic distortion (THD) and peak overshoot. The obtained converter output energizes the Brushless Direct Current Motor (BLDC) motor of EV after its conversion to AC form by a Voltage Source Inverter (VSI). A conventional PI controller is used for the effective speed control of BLDC motor. At times of power unavailability from PV systems, a VSI fed grid is used to energize the BLDC motor. Overall, the complete charging setup provides a constant power supply for EVs. The presented work is simulated using MATLAB and the output indicates the enhanced functioning of the charging system. Comparisons are carried out with existing converters and control approaches in which the proposed system delivers a reduced THD of 2.1% and an optimal efficiency of 97.6%.
Keywords: Lion Grey Wolf Optimized proportional integral (LGWO-PI) controller; Photovoltaic (PV) system; boost converter; brushless direct current (BLDC) motor; electric vehicle (EV) charging; proportional integral (PI) controller; single phase voltage source inverter (VSI); three phase VSI